Accounting, Analytical and Information Support for Law Enforcement Activity in Conditions of Ensuring Economic Security in Public Administration - Kryshtanovych , Myroslav; Lopatovskyi , Viktor; Bondaruk , Oleg; Datsii, Nadiia; Primush , Roman; Dragan, Ivan (Journal of Ecohumanism, 2024)
Objective: The objective of this study is to develop an effective model of accounting, analytical, and information support for law enforcement activities in ensuring economic security amidst strong turbulence in the external environment. Theoretical Framework: This research is anchored in the principles of economic security and law enforcement support systems. It utilizes the IDEF0 model as the primary theoretical framework to analyze and structure the accounting, analytical, and informational processes that underpin effective law enforcement in volatile conditions. Method: The research methodology employs the IDEF0 model to construct a comprehensive framework for the accounting, analytical, and information support systems specific to law enforcement activities. Results and Discussion: he study successfully resulted in a detailed decomposition of the IDEF0 model, highlighting innovative ways to bolster the accounting, analytical, and information support for law enforcement. These results are contextualized within the broader framework of maintaining economic security in turbulent environments, underscoring the adaptability and robustness of the proposed model. Research Implications: The practical and theoretical implications of this research are significant for policymakers and law enforcement agencies. The model provides a strategic foundation for enhancing economic security frameworks, which is crucial for adapting to and thriving in dynamic external conditions. Originality/Value: This study contributes original insights into the application of the IDEF0 model in a law enforcement context, particularly in scenarios characterized by significant economic turbulence.